A Load-Sharing Tissue Engineered Meniscus Scaffold: One Year Outcome. Issue 7 (29th July 2014) - Gatt, Charles J.; Patel, Jay Milan; Merriam, Aaron R.; Culp, Brian; Dunn, Michael G.
Objectives: Arthroscopic partial meniscectomy is one of the most commonly performed orthopaedic procedures. Although the procedure provides good symptom relief, long term follow up suggests the procedure results in an early onset of degenerative knee arthritis in a significant percentage of patients. Currently, treatment options for lost meniscal tissue are extremely limited and those available do not provide a long term solution. Therefore, there exists a need for a functional meniscus replacement in order to prevent joint deterioration. The objective of this project was to test a cross-linked collagen-hyaluronan sponge reinforced with synthetic, resorbable poly(DTD DD) fibers for meniscal implantation in an ovine model. Methods: Meniscus scaffolds were fabricated from poly(DTD DD) fibers woven into a semi-lunar wedge shape with extended tails for rigid tibial fixation. A dispersion of hyaluronic acid and type I bovine collagen was injected into the woven fiber scaffold. The scaffold was then lyophilized, crosslinked, and irradiated. The time-zero mechanical properties of the scaffold were evaluated with ultimate tensile testing and compression creep testing, and for load sharing function with a novel hoop stress evaluation and joint pressure distribution using Tekscan monitoring. The scaffolds were evaluated in an in vivo ovine model. A total medial meniscectomy was performed in the right hind leg of 30 sheep. Twenty-four of these sheep received a tissue engineered scaffold. The scaffold was anchored to the tibial plateau at the anterior and posterior root locations with titanium interference screws and sutured to the medial capsule. The remaining 6 sheep did not receive an implant and served as controls. Eight experimental and two control sheep were sacrificed at 16, 32 and 52 weeks. Scaffolds and adjacent articular cartilage underwent comprehensive mechanical and histological evaluation. Results: Pre-implantation characterization: Ultimate tensile strength of the implant was 660 N. The compressive modulus was 0.15 MPa. Hoop stress evaluation demonstrated a linear correlation between joint axial load and tensile stress in the implant. Tekscan evaluation demonstrated the implant increased joint contact area and decreased peak contact stress. In vivo evaluation demonstrated, at all time points, all 24 implants were fully intact and well healed to the surrounding capsule and maintained the meniscus-like shape (Figure 1). Gross and histological evaluation of the articular cartilage adjacent to the implant demonstrated minimal degenerative change in experimental knees. Control knees demonstrated advanced cartilage degradation adjacent to the meniscal resection. Robust tissue ingrowth into the implants was histologically demonstrated with tissue deposition occurring in a pattern consistent with tensile stresses in the implant. The tensile strength of the scaffold explant was 255 N at 16 weeks and 237 N at 32 weeks and 210 N at 52 weeks. The compressive modulus was 0.29 MPa at 16 weeks, 0.34 MPa at 32 weeks, and 0.49 MPa at 52 weeks. Conclusion: The results of this study support the feasibility of a tissue engineered load sharing scaffold for treatment of significant meniscal damage. The scaffold has the potential to prevent degenerative changes that occur after meniscectomy. Longer term studies will be necessary to confirm the true chondroprotective capabilities of this scaffold.